Cover Picture: Paenilamicin: Structure and Biosynthesis of a Hybrid Nonribosomal Peptide/Polyketide Antibiotic from the Bee Pathogen Paenibacillus larvae (Angew. Chem. Int. Ed. 40/2014). Issue 40 (30th July 2014) - Müller, Sebastian; Garcia‐Gonzalez, Eva; Mainz, Andi; Hertlein, Gillian; Heid, Nina C.; Mösker, Eva; van den Elst, Hans; Overkleeft, Herman S.; Genersch, Elke; Süssmuth, Roderich D.
<x xml:space="preserve">Abstract</x> American Foulbrood is a widespread and devastating disease of the honey bee brood caused by the bacterium Paenibacillus larvae. In their Communication on page 10821 ff., R. D. Süssmuth et al. elucidated a fascinating nonribosomal biosynthesis through the isolation and structure elucidation of the antibacterial and antifungal paenilamicins. Furthermore, examination of the secondary metabolites of P. larvae sheds light on the virulence mechanisms.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>